Reductive Cleavage Method for Quantitation of Monolignols and Low‐Abundance Monolignol Conjugates. Issue 10 (9th May 2018) - Regner, Matt; Bartuce, Allison; Padmakshan, Dharshana; Ralph, John; Karlen, Steven D.
Abstract: As interest in biomass utilization has grown, the manipulation of lignin biosynthesis has received significant attention, such that recent work has demanded more robust lignin analytical methods. As the derivatization followed by reductive cleavage (DFRC) method is particularly effective for structurally characterizing natively acylated lignins, we used an array of synthetic β‐ether γ‐acylated model compounds to determine theoretical yields for all monolignol conjugates currently known to exist in lignin, and we synthesized a new set of deuterated analogs as internal standards for quantification using GC–MS/MS. Yields of the saturated ester conjugates ranged from 40 to 90 %, and NMR analysis revealed the presence of residual unsaturated conjugates in yields of 20 to 35 %. In contrast to traditional selected‐ion‐monitoring, we demonstrated the superior sensitivity and accuracy of multiple‐reaction‐monitoring detection methods, and further highlighted the inadequacy of traditional standards relative to isotopically labeled analogs. Abstract : More than meets the eye : As plant breeding programs embrace the idea of the "biorefinery", lignin has come to be seen as a feedstock for commodity chemicals. Without robust analytics capable of describing lignin's chemical structure, its true value will remain hidden. To this end, a powerful analytical method was developed using synthetic methodology and isotopic labeling to identify new and low‐abundance monolignols and their conjugates.